Effect of Knowledge and Awareness on Cooperative Membership: Role of Socio-Demographic Profile in Cavite, Philippines - Manansala, Leo; Mendiola, Epitacio B. (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Membership in cooperatives is crucial for fostering collective strength and sustaining the organization, enhancing its ability to serve members effectively. By comprehending the factors influencing membership, cooperatives can develop targeted recruitment strategies, bridging gaps in effective recruitment and involvement in Philippine cooperatives. Purpose: This study delves into how knowledge and awareness levels impact cooperative membership while examining how socio-demographic factors like age, gender, education, and income moderate these relationships among members and non-members. Design/methodology/approach: Data from 764 respondents, including cooperative members and non-members from the top 30 cooperatives in Cavite, Philippines, binary logistic regression and diagnostic tests were utilized. Findings/ Results: The study reveals that educational initiatives are vital for promoting cooperative engagement, with higher knowledge levels significantly increasing the likelihood of membership. Demographic factors such as age and gender were found to moderate the influence of education and income on cooperative membership, indicating the need for more tailored and inclusive policies. The research shows that older individuals were less influenced by awareness efforts, while those with higher education were more likely to join cooperatives when well-informed. Although there were mixed effects of demographic factors on the relationship between awareness and membership, these effects were not statistically significant, suggesting that more detailed examination is needed.Conclusions: The study concludes that educational initiatives significantly enhance cooperative membership, particularly when tailored to specific demographic groups. Age and gender moderate the effect of knowledge and education, emphasizing the need for customized policies. However, further research is needed as demographic effects on awareness and membership were not statistically significant.Originality/ value (State of the art): The study stems from its novel examination of the interplay between knowledge, awareness, and socio-demographic factors in influencing cooperative membership, particularly in Philippine cooperatives. It adds value in providing actionable insights for cooperative policymakers, enabling the design of more targeted, inclusive recruitment strategies that address demographic diversity and promote sustainable cooperative growth. Keywords: customized policies, demographic factors, cooperative engagement, cooperative membership, Philippines